Assessment of the current climate and expected climate changes in the Metropolitan Region of Santiago de Chile - Gonzalo Cortés; Sven Schaller; Maisa Rojas; Lilian Garcia; Aniella Descalzi; Luis Vargas; James McPhee (Helmholtz-Zentrum für Umweltforschung (UFZ), 2012)
This report describes the methodology and results from the analysis of climate scenarios and their impact on hydrometeorological variables in the Metropolitan Region of Santiago de Chile (MRS). Using a downscaling methodology for future scenarios A2 and B1, according to IPCC, temperature, precipitation and secondary variable trends were estimated for the time-window 2045-2065. The main results predict that Santiago will be a dryer and hotter city in the near future, with a high number of days with extreme temperatures. Due to lower precipitation rates, decreasing magnitudes in the streamflow of the two main rivers, Maipo and Mapocho, are expected. The presented data provide a basis for the ClimateAdaptationSantiago (CAS) project as the aim of that project is to elaborate, evaluate and prioritize adaptation measures to the climate change in the MRS.
Keywords: 330; Klimaveränderung; Prognose; Santiago (Chile)